Hydrogels for the Delivery of Plant-Derived (Poly)Phenols - Nicola Micale; Andrea Citarella; Maria Sofia Molonia; Antonio Speciale; Francesco Cimino; Antonella Saija; Mariateresa Cristani (Molecules, 2020)
This review deals with hydrogels as soft and biocompatible vehicles for the delivery of plant-derived (poly)phenols, compounds with low general toxicity and an extraordinary and partially unexplored wide range of biological properties, whose use presents some major issues due to their poor bioavailability and water solubility. Hydrogels are composed of polymeric networks which are able to absorb large amounts of water or biological fluids while retaining their three-dimensional structure. Apart from this primary swelling capacity, hydrogels may be easily tailored in their properties according to the chemical structure of the polymeric component in order to obtain smart delivery systems that can be responsive to various internal/external stimuli. The functionalization of the polymeric component of hydrogels may also be widely exploited to facilitate the incorporation of bioactive compounds with different physicochemical properties into the system. Several prototype hydrogel systems have been designed for effective polyphenol delivery and potential employment in the treatment of human diseases. Therefore, the inherent features of hydrogels have been the focus of considerable research efforts over the past few decades. Herein, we review the most recent advances in (poly)phenol-loaded hydrogels by analyzing them primarily from the therapeutic perspective and highlighting the innovative aspects in terms of design and chemistry.